Traceability of the hygienic quality of the public water supply along the supply chain in the shantytowns of the sixth district of cotonou (south Benin) - HOUNSOUNOU, Espérance; AGASSOUNON DJIKPO TCHIBOZO, Micheline; AYI-FANOU, Lucie; KELOME, NC; VISSIN, Expédit; MENSAH, Apollinaire (My University, 2019)
In Benin, many households in the shantytowns of the sixth district of Cotonou have resorted to public water retailers for domestic uses. In order tomonitor the quality of this water on the supply chain, a study was carried out at three levels (tap, transport and storage) in June 2015 and February 2016on 60 samples. The usual physicochemical parameters were measured in situ. Indicators of microbial contamination (Revivifiable aerobic flora, Sulfito-reducer anaerobic (ASR), Total Coliforms (CT), Thermotolerant Coliforms (Cth) and Esherichia coli were investigated by standardized methods. The results of physicochemical parameters such as temperature, pH and turbidity are out of range along the water supply chain. Of the 12 samples taken at the tap, four (4) water samples were non-compliant. For the transported water samples, the FAR, CT, Cth and E. coli values varied from <1 to 3.38 • 102 CFU, respectively; <1 to 2.98 • 102CFU ;<1 to 2.41.102 CFU; <1 to 6.1.101 CFU. In stored waters, they range from <1 to 6.103 CFU; <1 and 4.6.103 CFU; <1 and 1.7.103 CFU; <1 and 5.101 CFU respectively for FAR, CT, Cth and E. coli. Except the ASR that are absent, the results show a bacterial increase ranging from 16.67% to 100% on the supply chain. The non-standard WHO values and Beninese normative criteria are mainly at the level of transport and storage. The lack of hygiene is at origin of the contamination of the water along the chain.
Keywords: public water -Tracability-Quality-Water chain-hygiene